Towards sustainable cities: Evaluating the distribution and functionality of green spaces in Atakum - Uslu, Deniz Yıldız; Almansouri, Hafith Mohammed Sulayman; Elahsadi, Amragia H. Mostafa; Cetin, Mehmet (Journal of Design for Resilience in Architecture & Planning, 2024)
The rapid increase in urbanization has led to a concentration of population and buildings, resulting in reduced green spaces and disrupted ecological balance. This trend negatively affects the well-being and quality of life in cities. Designing green spaces according to planning standards and protecting these areas is crucial for the sustainability of urban environments and the preservation of livable spaces for future generations. In light of these challenges, it is vital to preserve and expand green spaces for both environmental and social reasons. This study aims to evaluate the spatial distribution, size, and adequacy of existing green spaces in 16 neighborhoods of Atakum, a district in Samsun that has recently undergone intense urbanization. It also assesses the accessibility of these spaces using Geographic Information Systems (GIS). The analysis of urban green spaces in Atakum was conducted through spatial and buffer zone analyses using the Spatial Analyst tool in ARCGIS 10.7, revealing the current situation of these vital areas. The findings highlight the significance of green spaces in ensuring livable and sustainable urban development, especially in rapidly urbanizing areas. The research identifies substantial disparities in the distribution and accessibility of open and green spaces in Atakum, indicating an urgent need for improved urban planning. Using GIS analysis, the study compares the availability of green spaces against the World Health Organization’s recommended standard of 10 m² per person. Results show that many neighborhoods fall short of this benchmark, a situation exacerbated by rapid urbanization and population growth. This deficit adversely impacts residents' physical and mental well-being, as adequate green space is essential for public health, social cohesion, and environmental sustainability. Additionally, the analysis reveals that existing green spaces primarily serve recreational purposes and lack multifunctionality, limiting their usability for diverse community needs. To address these deficiencies, the study recommends a multi-faceted urban planning approach, emphasizing the equitable distribution of green spaces, the design of multifunctional areas, and robust community engagement in the planning process. It also stresses the need for stronger legal frameworks to preserve and create green spaces, advocating for the integration of research and data analysis to inform evidence-based policies. In conclusion, this research contributes to understanding how urban green spaces can enhance livability, particularly in the context of climate resilience. The findings underscore the importance of strategic planning in fostering sustainable and inclusive urban environments in Atakum, offering valuable insights for future urban studies in similar contexts.
Keywords: multifunctional areas; Building construction; equity in green space distribution; open and green spaces; Architecture; urbanization; NA1-9428; TH1-9745; urban planning